Karyotype Analysis of Phalaenopsis Hibryds with Colchicine Induction - Sri Hartati; Samanhudi Samanhudi; Hasna Afanin (Journal of Biodiversity and Biotechnology, 2024)
Phalaenopsis hybrid is one of the orchids that is very important in the horticultural market as an ornamental plant whose demand continues to increase. This causes the need for breeding in order to obtain new varied flower characters as desired by polyploidization. Polyploidy induction in Phalaenopsis hybrids was carried out using colchicine. The purpose of this study was to determine the karyotype pattern of Phalaenopsis hybrids. The research was conducted at the Screenhouse of the Faculty of Agriculture and Integrated Laboratory Unit of Sebelas Maret University, Surakarta in August 2021-March 2022. Polyploidy induction was carried out by dripping 1500 ppm concentration of colchicine on flower bud of Phalaenopsis hybrid. The method used in this research is squashing. The experimental results showed that the karyotype pattern in control Phal. Golden Tree was 2n=3x-7=50m, while in Phal. Fuller Sunset and Phal. OX X-ray was 2n=4x=76m. The karyotype pattern in orchids with colchicine induction was Phal. Golden Tree 2n=6x-14=100m, while in Phal. Fuller Sunset and Phal. OX X-ray 2n=8x=152m.